Variations in skin colour and the biological consequences of ultraviolet radiation exposure. (4th October 2013) - Del Bino, S.; Bernerd, F.
Abstract : What's already known about this topic? Sun exposure sensitivity is largely dependent on the degree of skin constitutive pigmentation. What does this study add? The individual typology angle (ITA)‐based skin colour classification correlates with constitutive pigmentation and is physiologically relevant in different geographical areas. It may help identify differential responses to ultraviolet radiation (UVR) exposure that correspond to particular skin colour type's UVR sensitivities. It supports the concept of personalized photoprotection. Summary: Harmful consequences of sun exposure range from sunburn, photoageing and pigmentary disorders to skin cancer. The incidence and extent of these detrimental effects are largely due to the degree of constitutive pigmentation of the skin. The latter can be objectively classified according to the individual typology angle (°ITA) based on colorimetric parameters. The physiological relevance of the ITA colorimetric classification was assessed in 3500 women living in various geographical areas. Furthermore, in order to understand the relationship between constitutive pigmentation and ultraviolet radiation (UVR) sensitivity, we worked on ex vivo human skin samples of different colour exposed to increasing UVR doses. For each sample we defined the biologically efficient dose (BED), based on the induction of sunburn cells, and analysed UVR‐induced DNA damage (cyclobutane thymine dimers, CPD). We found a significant correlation between ITA and BED. We also found a correlation between ITA and DNA damage. As the epidermal basal layer also hosts melanocytes and in order to analyse the relationship between skin colour and DNA damage occurring specifically within this cell type, we performed double staining for CPD and tyrosinase‐related protein (TRP) 1, a key enzyme in melanin synthesis. We found that DNA damage within melanocytes depends on ITA. Taken together our results may explain the higher risk of lighter skin types developing skin cancers, including melanoma, as well as the development of pigmentary disorders in moderately pigmented skin. They show that skin classification based on ITA is physiologically relevant (as it correlates with constitutive pigmentation) and further support the concept of a more personalized approach to photoprotection that corresponds to a particular skin colour type's sensitivity to solar UVR.